Antimicrobial and immune modulatory effects of lactic acid and short chain fatty acids produced by vaginal microbiota associated with eubiosis and bacterial vaginosis - Aldunate, Muriel; Srbinovski, Daniela; Hearps, Anna C.; Latham, Catherine F.; Ramsland, Paul A.; Gugasyan, Raffi; Cone, Richard A.; Tachedjian, Gilda (Frontiers in Physiology, 2015)
Lactic acid and short chain fatty acids (SCFAs) produced by vaginal microbiota have reported antimicrobial and immune modulatory activities indicating their potential as biomarkers of disease and/or disease susceptibility. In asymptomatic women of reproductive-age the vaginal microbiota is comprised of lactic acid-producing bacteria that are primarily responsible for the production of lactic acid present at ~110 mM and acidifying the vaginal milieu to pH ~3.5. In contrast, bacterial vaginosis (BV), a dysbiosis of the vaginal microbiota, is characterized by decreased lactic acid-producing microbiota and increased diverse anaerobic bacteria accompanied by an elevated pH>4.5. BV is also characterized by a dramatic loss of lactic acid and greater concentrations of mixed SCFAs including acetate, propionate, butyrate and succinate. Notably women with lactic acid-producing microbiota have more favorable reproductive and sexual health outcomes compared to women with BV. Regarding the latter, BV is associated with increased susceptibility to sexually transmitted infections (STIs) including HIV. In vitro studies demonstrate that lactic acid produced by vaginal microbiota has microbicidal and virucidal activities that may protect against STIs and endogenous opportunistic bacteria as well as immune modulatory properties that require further characterization with regard to their effects on the vaginal mucosa. In contrast, BV-associated SCFAs have far less antimicrobial activity with the potential to contribute to a pro-inflammatory vaginal environment. Here we review the composition of lactic acid and SCFAs in respective states of eubiosis (non-BV) or dysbiosis (BV), their effects on susceptibility to bacterial/viral STIs and whether they have inherent microbicidal/virucidal and immune modulatory properties. We also explore their potential as biomarkers for the presence and/or increased susceptibility to STIs.